UTILIZATION OF EST-SSR MARKER FOR THE GENERATION OF ADDITIONAL DESCRIPTOR FOR THE IDENTIFICATION OF ELITE MATERIAL IN CASTOR (Ricinus communis L.) - GOURI SHANKAR V, GOUTHAMI PALLE, RAMESH THATIKUNTA, NARENDER REDDY S, DURGA RANI CH. V and (The Journal of Research, PJTSAU, 2019)
Oilseeds occupy a pride place in Indian economy next to food grains. Castor (Ricinus communis L.) plays an important role in the country’s vegetable oil economy. India accounts for 59% of global castor area and 81% of world castor production and ranks first in area and production in the world.